ChemInform Abstract: Heterogeneously Catalyzed Alcohol Oxidation for the Fine Chemical Industry. Issue 4 (January 2016) - Ciriminna, Rosaria; Pandarus, Valerica; Beland, Francois; Xu, Yi‐Jun; Pagliaro, Mario
Abstract: Review: 56 refs.